Manuver Epley dan Brandt-Daroff Dalam Penatalaksanaan Benign Paroxysmal Positional Vertigo (BPPV) - Hafidah, Hazima Hasna; Marcellia, Selvi; Apriliana, Ety (Medula, 2025)
Benign Paroxysmal Positional Vertigo (BPPV) is the most common cause of vertigo with a case prevalence of 1.6% globally. It is characterized by recurrent episodes of vertigo due to changes in head position. BPPV disease is caused by the transfer of otoconia to the semicircular canal, stimulating the vestibulocochlear nerve resulting in symptoms of vertigo, nystagmus, and becoming more sensitive to head movement. The impact is significant on the physical, psychological, and quality of life aspects of the patient. This literature review discusses the mechanism, effectiveness, and success rate of Epley and Brandt-Daroff maneuvers. Data were obtained from relevant literature with data sources coming from Pubmed, NCBI, and Google Scholar.  The results of the literature review showed that the Epley maneuver has high effectiveness with a cure rate of up to 92% within one week and a significant reduction in sequelae, especially in the modified Epley maneuver. In addition, the Brandt-Daroff maneuver proved to be effective for self-treatment at home with gradual improvement of vertigo symptoms. Both methods have advantages, such as the flexibility of the Brandt-Daroff maneuver and quick results in the Epley maneuver, but have certain limitations in patients with comorbid conditions. The conclusion of this literature review shows that the Epley maneuver is the first choice in the treatment of BPPV due to its higher effectiveness, while the Brandt-Daroff maneuver can be used as an alternative.